Newer drugs in the management of diabetes mellitus - Deshmukh, Vinod S.; Motghare, Vijay M.; Padwal, Sudhir L.; Jaykare, Swapnil; Patil, Jyoti; Pise, Harshal (International Journal of Basic & Clinical Pharmacology, 2017)
Modern life style with present days technological advances have made human life sedentary. This is causing increasing prevalence of obesity and physical inactivity amongst population. The number of cases of diabetes worldwide in the year 2000 among adults 20 years of age is estimated to be 171 million in recent reports and is said to rise to more than 300 million by 2025. The raised plasma glucose levels give rise to complications in the form of microvascular and macrovascular complications diminished quality of life with reduced life expectancy. The currently available drugs used in the management of type II DM are not completely satisfactory in regard of controlling blood glucose level, many of the times they are associated with undesirable side effects. Hence there is continuous ongoing work in development of newer drugs, which are safe, efficacious and potent as well as free of undesirable effects such as sustained hypoglycaemia. Fortunately there are newer drug, few of them approved while other still knocking the door from the classes of drug such as GLP-1Mimetic, DPP-4 Inhibitors and others. Here we have tried to cover them in brief.